System and Method for Quantum Key Distribution - Sellami , Ali; Witjaksono, Gunawan; Wahiddin, Mohamed Ridza (2012)
A system and method of quantum key distribution between a transmitter (100) and a receiver (200), wherein the system comprises at least one transmitter (100), at least one receiver (200, and a transmission means (26) for sharing a secret key securely through the means of generating quantum signals in random phase modulation and random frequency modulation, in an increased length of key.